Exploring the dimensionality of the 5C positive youth development very short form using Rasch measurement theory in Swedish upper secondary school contexts - Johanna Bergman; Maria Haak; Petra Nilsson Lindström; Åsa Bringsén; Albert Westergren (PLoS ONE, 2025)
The 5C Positive Youth Development Very Short Form (PYD-VSF) was designed as a user-friendly tool to assess positive youth development. This study examined the dimensionality using Rasch measurement theory on data from 430 upper secondary school pupils in southern Sweden. A Swedish version of the tool was developed through dual-panel translation and cognitive interviews. Findings from psychometric testing indicated multidimensionality, showing support for a post hoc two-dimensional structure with the following components: Self-worth ( Competence , Confidence, and Connection ) and Pro-social ( Character and Caring) . These two constructs were distinct yet related, suggesting that Self-worth may be a prerequisite for Pro-social development. Systematic gender variance was also observed, although with a negligible impact on score interpretation. The identified constructs align with ongoing discussion about agency and resilience in relation to young persons’ health. Further research is recommended within the PYD framework, with priority given to the use of standardised and validated instruments to clarify how these constructs may both strengthen young persons in the present and buffer against future adverse outcomes.